SPIONs as theranostic agents in bladder and prostate cancer: integrating diagnosis and therapy - Li, Dezheng; Wu, Weilian; Liu, Haicheng; Lou, Kecheng (Frontiers in Nanotechnology, 2025)
Superparamagnetic iron oxide nanoparticles (SPIONs) have emerged as transformative theranostic platforms in urological oncology. This review systematically synthesizes literature from PubMed, Web of Science, and Scopus (2010–2024) to evaluate SPION-based strategies for bladder cancer (BCa) and prostate cancer (PCa). We highlight their role in enhancing diagnostic precision (e.g., PSMA-targeted MRI, sentinel lymph node navigation) and enabling innovative therapies (e.g., magneto-photothermal synergy, ferroptosis immunomodulation). Key advantages include superior targeting, multimodal imaging capability, and the ability to overcome physiological barriers such as the blood-prostate and blood-urine barriers. While preclinical results are promising, clinical translation requires addressing biosafety, scalable production, and regulatory hurdles. SPIONs represent a robust alternative to conventional therapeutics, particularly in settings requiring precision and combinatory approaches.